Penerapan Metode K-means Pada Klasterisasi Provinsi di Indonesia Berdasarkan Indikator Indeks Kebahagiaan - Damayanthi, Ni Wayan Rita; Suciptawati, Ni Luh Putu; Jayanegara, Ketut; Sukarsa, I Komang Gde; Kencana, Eka N.; Wijayakusuma, I Gusti Ngurah Lanang (Jurnal Matematika, 2024)
The happiness index is a measure that reflects individual well-being, thus playing an important role in the development of a region. The level of happiness in Indonesia is still significantly lower compared to other ASEAN countries. In relation to efforts to improve the happiness index in Indonesia, this study applies the K-means method to cluster the 34 provinces of Indonesia based on the indicators of the happiness index for the year 2021. The data used is sourced from publications by the Indonesian Central Bureau of Statistics with seven happiness index indicators and employing the Minkowski distance. The clustering results of the 34 provinces using the K-means method obtained four clusters with a cluster accuracy value of 71 percent. Cluster 1 consists of seven provinces with a fairly high average of seven attributes, cluster 2 consists of seven provinces is a cluster with a low average level of internal and external satisfaction, cluster 3 consists of four provinces with a high average of seven attributes, and cluster 4 consists of 16 provinces is a cluster with provinces with a fairly high average level of external satisfaction, but a low level of internal satisfaction.